2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8462102
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Negative Symptoms of Schizophrenia from Emotion Related Low-Level Speech Signals

Abstract: Negative symptoms of schizophrenia are often associated with the blunting of emotional affect which creates a serious impediment in the daily functioning of the patients. Affective prosody is almost always adversely impacted in such cases, and is known to exhibit itself through the low-level acoustic signals of prosody. To automate and simplify the process of assessment of severity of emotion related symptoms of schizophrenia, we utilized these low-level acoustic signals to predict the expert subjective rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The cognitive models applied the Addenbrooke’s Cognitive Examination-Revised, the picture naming task (International Picture Naming Project, IPNP), the National Adult Reading Test (IPNP), and so on, accompanied by a one-time MRI scan and an in-depth neuropsychological assessment. In addition, Chakraborty and colleagues22 investigated into patients with schizophrenia who were unable to identify emotion from voice due to their incapability in understanding low-level acoustic features, such as pitch, intensity, frequency, and so forth. The Negative Symptom Assessment-16 scale23 rating method evaluated the behavior of those 78 participants (52 patients and 26 controls).…”
Section: Resultsmentioning
confidence: 99%
“…The cognitive models applied the Addenbrooke’s Cognitive Examination-Revised, the picture naming task (International Picture Naming Project, IPNP), the National Adult Reading Test (IPNP), and so on, accompanied by a one-time MRI scan and an in-depth neuropsychological assessment. In addition, Chakraborty and colleagues22 investigated into patients with schizophrenia who were unable to identify emotion from voice due to their incapability in understanding low-level acoustic features, such as pitch, intensity, frequency, and so forth. The Negative Symptom Assessment-16 scale23 rating method evaluated the behavior of those 78 participants (52 patients and 26 controls).…”
Section: Resultsmentioning
confidence: 99%
“…1) Pitch-related features: Pitch is the fundamental frequency of vocal cord vibration for voiced initial consonants and some unvoiced initial consonants [35]. Pitchrelated features are common used in analyzing flat affect of negative symptoms [24,25,26,27,28,29,30,3]. Studies [28,27,26,24] demonstrated that schizophrenia speech characterized by less variability in vocal pitch than normal speech.…”
Section: Related Workmentioning
confidence: 99%
“…Spectrum-related features are commonly used for schizophrenia speech analysis, reflecting the energy distribution and the vocal tract characteristics during speech production. The typical spectrum-related features, such as formants, auditory-based spectral features, and spectral envelope features, had been proved to be an effective feature for schizophrenia speech detection [28,33,29,34]. 1) Formants: Formant is the descriptor that reflects the resonance frequency of the vocal tract.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations